Ucinnost perorálnĕ podaného ivermektinu proti larválním stadiím strecka srncího (Hypoderma diana B.) u srncí zvĕre - Lamka, J; Suchý, J; Staud, F (Veterinarni medicina, 1996)
Hypodermosis and cephenemyiosis are largely widespread diseases in roe deer in the conditions of the Czech Republic. Both kinds of parasitosis cause great losses of game. The aim of this study was to test peroral administration of ivermectin with respect to the control of larval stages of hypodermosis (Hypoderma diana B.) in roe deer. Studies were performed on three localities within one three-year study and two 18-month studies. Ivermectin was administered for two days at a daily dose of 0.30 mg/kg body weight during winter game feeding. The shot deer were checked for the presence of larvae throughout the year. Prevalence and intensity of infection were determined. A total of 147 animals were checked in 1992-1994 (Tab.I); prevalence and intensity of infection were very low in comparison with the situation before treatment and with the control group (1994). Similar results were obtained in both shorter studies (Tab. II) performed on 27 animals in total. The results suggest (on the base of detail discussion) that the low values of prevalence and intensity of infection should be taken as partly distorted due to the methodical conditions of checks. The efficacy of ivermectin treatment was complemented by observation of several cases and their results employing direct checks of shot deer (Tab. III), including a six-year observation of a group of 6 to 10 individuals of tame deer treated year by. These results explicitly document the high efficacy of mass peroral ivermectin administration in the control of warble fly larvae. Ivermectin is the first drug suitable for the treatment of roe deer hypodermosis.
Keywords: hypodermyiáza; Administration, Oral; larva; insekticidy; Larva; Insecticides; Ivermectin; aplikace orální; zvířata; vysoká zvěř; Diptera; ivermektin; Hypodermyiasis; Deer; Animals